Chemistry Students’ Cognitive Styles and Academic Achievement in Secondary Schools in Nigeria - Nwafor, Stephen Chinedu; Odukwe, Ogochukwu Chinelo; Aghamelu, Ogonna Somtochukwu; Muoneke, Nneora Mary (RADINKA JAYA UTAMA PUBLISHER, 2024)
The study examined the relationship between the cognitive styles of secondary school students in the Awka Education Zone of Anambra state, Nigeria, and their academic achievement in Chemistry. It also considered the moderating influence of gender on the relationship between these variables. A Chemistry Achievement Test (CAT) proforma and the Group Embedded Figure Test (GEFT) were the two instruments used to collect the data. The study problems were addressed using the Pearson product moment coefficient (r), coefficient of determination (r2), linear regression and the Hayes Macro Process with the hypotheses tested at the 0.05 level of significance. The findings showed a strong positive correlation between secondary school students' academic achievement in Chemistry and their cognitive styles. Additionally, there is a moderately significant positive relationship between a student's gender and their academic achievement in Chemistry at the secondary school level in terms of cognitive style. Among other things, it was suggested that chemistry lessons be designed to identify each student's preferred cognitive style and work to meet their needs. Also, Chemistry pre-service and in-service teachers should be trained to create appropriate classroom environment that integrates variables such as cognitive styles and gender unbiased teaching method in the learning process.